WYBRANE KARNOPROCESOWE ASPEKTY ŚCIGANIA PRZESTĘPSTW PRZECIWKO WŁASNOŚCI INTELEKTUALNEJ - Gerecka-Żołyńska, Anna (Wydział Prawa i Administracji UAM, 2005)
The purpose of this article is an evaluation of penal procedure institutions which have some influence on intellectual property protection or are only related to it. The article shortly presents the impact of the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS) (especially its rule 61) on intellectual property protection. It also discuses some Polish Criminal Procedure Law institutions related to intellectual property protection. Many institutions are still controversial despite the imposition of the industrial property act in 2001 and the revision of the act on copyright and similar rights in 2000. Some controversial institutions presented in this paper include: public action implementation mainly on victim demand, determination of persons who have the right to conduct preparatory proceedings, evidence material gathering and protection especially with respect to offence commonly referred to as piracy (industrial or intellectual). A presentation of the role of preliminary procedures is also offered, as it has been gaining in significance in the western European model of intellectual property protection.
SELECTED ASPECTS OF PROSECUTING INTELLECTUAL PROPERTY VIOLATIONS